Dual-specificity phosphatase 1: a critical regulator of innate immune responses. (25th October 2006) - Abraham, S.M.; Clark, A.R.
Abstract : Innate immune responses are critically dependent on MAPK (mitogen-activated protein kinase) signalling pathways, in particular JNK (c-Jun N-terminal kinase) and p38 MAPK. Both of these kinases are negatively regulated via their dephosphorylation by DUSP1 (dual-specificity phosphatase 1). Several pro- and anti-inflammatory stimuli converge to regulate the DUSP1 gene and to modulate the time course of its expression. In turn, the pattern of expression of DUSP1 dictates the kinetics of activation of JNK and p38 MAPK, and this influences the expression of several mediators of innate immunity. DUSP1 is therefore a central regulator of innate immunity, and its expression can profoundly affect the outcome of inflammatory challenges. We discuss possible implications for immune-mediated inflammatory diseases and their treatment.